Karl Rahner’s “Remarks on the Schema, ‘De Ecclesia in Mundo Hujus Temporis,’ in the Draft of May 28, 1965” - O'Meara, Thomas F. (Philosophy & theology, 2008)
The author acquired in May of 1965 a copy of Karl Rahner’s observations on the latest draft of “Schema XIII” which would become Gaudium et Spes. The title was “Anmerkungen zum Schema DE ECCLESIA IN MUNDO HUIUS TEMPORIS (in der Fassung vom 28.5.65).” After the third session of Vatican II serious work remained to be done on that text. Among several meetings was one long and important occurred at Ariccia in the Alban hills outside Rome. Rahner could not attend because he could not miss so many lectures at the University of Munich. He sent written comments. That document is a valuable source for the research of the theological background of Gaudium et Spes. Rahner’s observations fall into three subheadings: remarks on the Latin syntax and style; general observations on the underlying theological principles; detailed observations on particular points.